Innovative Agricultural Financing Models to Enhance Farmers’ Access to Sustainable Credit and Investment - Widi, Riantin Hikmah; Suprapto, Agus; Ellyta (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Farmers’ access to sustainable finance remains a persistent structural barrier to agribusiness development in many developing countries. In Indonesia, conventional credit schemes often fail to align with the seasonal nature and risk profile of agriculture, limiting productivity and financial inclusion among smallholder farmers. This study aims to evaluate innovative financing models that can improve access to credit and sustainable investment in three agrarian regions: Kulon Progo, Jember, and Tanah Datar. Using a qualitative multiple case study approach, the research examines the design and implementation of value chain financing, blended finance mechanisms, and digital lending platforms within varying local agricultural contexts. The findings reveal that value chain financing in Kulon Progo significantly reduced non-performing loan rates to 1.2%; digital lending in Jember reached over 3,200 young farmers; and blended finance in Tanah Datar contributed to a 26% increase in household income. These results highlight the importance of coordination among agribusiness actors, financial institutions, and enabling policy frameworks. The study contributes practical insights for policymakers by identifying key success factors such as adaptive regulation, improved digital infrastructure, and institutional partnerships needed to scale inclusive financing models and enhance the resilience of Indonesia’s smallholder farmers.